A Critical Analysis of the 2018 GCE Ordinary Level English Language Paper in Sri Lanka - Jayaweera, C. (University of Jaffna, 2025)
Language tests are administered worldwide, and their pros and cons can be identified from both the test takers and designers. A good language test should be practical, comprehensive, relevant, and balanced, with a degree of difficulty that is neither too hard nor too easy. It should assess both linguistic and communicative competence, with clear instructions and real-world relevance. The ultimate goal of language teaching is achieving communicative competence, particularly speaking skills. This analysis evaluates the 2018 GCE Ordinary Level English language paper in Sri Lanka, focusing on its validity, reliability, practicality, and alignment with the syllabus objectives. A comparative analysis was conducted between the test content and the prescribed syllabus objectives to identify gaps, highlighting areas where the test fails to adequately reflect the curriculum’s goals and objectives. This method enabled a detailed evaluation of the alignment between what is taught and what is tested, uncovering discrepancies in skill emphasis and topic coverage. The test predominantly assesses reading and writing, neglecting speaking and listening skills, and fails to meet the broader goals of the curriculum. While it exhibits some strengths in clarity, consistency, and reliability, several aspects, such as content validity, construct validity, and the testing of communicative competence, are found lacking. The test’s design introduces negative backwash effects on the educational system, and its length, repetitive nature, and unrealistic time constraints detract from its practicality. The paper does not adequately reflect the content taught in the syllabus, and there is a noticeable imbalance in the proportion of skills tested. Suggestions for improvement include incorporating listening and speaking components, rebalancing the content, and adjusting the test format and time allocation to better align with the objectives of the curriculum.
Keywords: Language testing; Communicative competence; Curriculum alignment; Test validity and reliability; English language assessment